Assessment of Antiplasmodial and Antioxidant Activities, Total Phenolics and Flavonoids Content, and Toxicological Profile of Cola millenii K. shum (Malvaceae) - LAGNIKA, LATIFOU (My University, 2020)
Aims: This study was designed to assess antiplasmodial and antioxidant activities in relation to phytochemical contents and toxicological profile of crude extracts of Cola millenii leaves. Place and Duration of Study: The study was carried out from April 2015 to November 2018 at University of Abomey-Calavi, Laboratory of Biochemistry and Bioactives Natural Products and Laboratory of Infectious Vector-borne Diseases. Methodology: Phytochemical screening of aqueous and ethanolic crude extracts was performed using standard methods. Estimation of total phenolics contains (TPC) and total flavonoids contains (TFC) was done using colorimetric methods. Antioxidant activity was assessed in vitro by 2,2- diphenyl-1-picrylhydrazyl (DPPH) Radical-Scavenging, Reducing power, superoxide radical scavenging and Hydrogen peroxide scavenging assay. Antiplasmodial activity was investigated in vitro using both field isolate and laboratory 3D7 strains of P. falciparum using Plasmodium lactate dehydrogenase (pLDH) assay. Hemoglobin release was measured spectrophotometrically to assess hemolytic power. Acute oral toxicity of extracts was evaluated on rats according to OECD 423 guideline. Results: Flavonoids, anthraquinones, coumarins, and triterpenes were recorded in both extracts while tannins were recorded only in ethanolic extract. High TPC and TFC were recorded with ethanolic extract with significate difference (P <0.01) when compared to aqueous extract. Ethanolic extract exhibited the highest parasite growth inhibition against both field isolate (41.62±1.78%) and 3D7 (45.89±1.66%) strains at 100 μg/mL. Both extracts exhibited strong antioxidant activity according to different methods used. Toxicological profile revealed no hemolytic effect on human red blood cells as well as acute toxicity signs in rats. Conclusion: This study demonstrated strong antioxidant and moderate antiplasmodial activities of C. millenii extracts without toxicity effect on rats and human erythrocytes. It would play an important role in malaria and oxidative damage control.
Keywords: Cola millenii; phytoconstituents; antioxidant activity; antiplasmodial activity; toxicity.